2023
DOI: 10.1039/d3cy00116d
|View full text |Cite
|
Sign up to set email alerts
|

The selective oxidation of methane to methanol using in situ generated H2O2 over palladium-based bimetallic catalysts

James H. Carter,
Richard J. Lewis,
Nikolas Demetriou
et al.

Abstract: The selective oxidation of methane to methanol, using H2O2 generated in situ from H2 and O2 has been investigated using a series of TS-1 supported bimetallic palladium-based catalysts. The alloying...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The best-performing catalyst (0.2Au0.5FeHS, further written as AuFeHS) had an optimum Fe concentration of 0.46 wt % and an Au concentration of 0.23 wt %, confirmed by inductively coupled plasma-optical emission spectrometry (ICP-OES). Hydrophobic support is important in oxidation reactions involving H 2 O 2 because it helps peroxide to be close to the active sites of Au and Fe, where incoming methane can react with peroxide efficiently. , Further, it is known that the active sites get blocked in the hydrophilic conditions because of the presence of moisture, and it is also known that the Au particle size increases in the aqueous conditions, which further lowers the activity of the catalyst. A hydrophobic environment also facilitates easy desorption of the methanol from the surface, preventing overoxidation. , The hydrophobicity of silica was confirmed by contact angle analysis with an observed angle of 118° (Figures S1 and S2). The C–H vibration from silica confirmed hydrophobic functionalization from HS (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best-performing catalyst (0.2Au0.5FeHS, further written as AuFeHS) had an optimum Fe concentration of 0.46 wt % and an Au concentration of 0.23 wt %, confirmed by inductively coupled plasma-optical emission spectrometry (ICP-OES). Hydrophobic support is important in oxidation reactions involving H 2 O 2 because it helps peroxide to be close to the active sites of Au and Fe, where incoming methane can react with peroxide efficiently. , Further, it is known that the active sites get blocked in the hydrophilic conditions because of the presence of moisture, and it is also known that the Au particle size increases in the aqueous conditions, which further lowers the activity of the catalyst. A hydrophobic environment also facilitates easy desorption of the methanol from the surface, preventing overoxidation. , The hydrophobicity of silica was confirmed by contact angle analysis with an observed angle of 118° (Figures S1 and S2). The C–H vibration from silica confirmed hydrophobic functionalization from HS (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophobic support is important in oxidation reactions involving H 2 O 2 because it helps peroxide to be close to the active sites of Au and Fe, where incoming methane can react with peroxide efficiently. 31,32 Further, it is known that the active sites get blocked in the hydrophilic conditions because of the presence of moisture, and it is also known that the Au particle size increases in the aqueous conditions, which further lowers the activity of the catalyst. 33−35 A hydrophobic environment also facilitates easy desorption of the methanol from the surface, preventing overoxidation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These include poor selective H 2 utilization, rapid catalyst deactivation, and the formation of complex product mixtures, necessitating extensive purification and the inclusion of promoters. Indeed, in many cases, it is the presence of H 2 , required to generate H 2 O 2 in situ, that largely promotes the formation of such byproducts. , Such concerns are not limited to alkene epoxidation, with product distributions for a range of transformations influenced by competitive unselective hydrogenation pathways. , It is the overcoming of these challenges that has motivated extensive research from our laboratory, with particular focus placed on the application of Pd-based catalysts for (i) alkane upgrading, (ii) alcohol oxidation, , and recently (iii) the ammoximation of cyclohexanone (and other cyclic ketones) to the corresponding oxime. ,, Regarding alkane oxidation, we direct the reader to our recent Account on methane valorization for an extensive discussion of our contribution to this field …”
Section: Challenging Current Industrial Processesmentioning
confidence: 99%
“…14,15,16,17,18 To address the issue of overoxidation by excessive amount of H2O2, the in situ synthesis of H2O2 from H2/O2 mixtures, catalyzed by AuPd bimetallic nanoparticles, has been integrated into CH4 oxidation processes. 19,20,21,22,23,24,25 Nonetheless, the cost of catalysts/oxidants and the employment of hazardous chemicals have limited the utility of those process.Recently, electrocatalytic conversion of CH4 has been reported, bringing advantages like mild reaction condition and innovative reaction pathway. 26,27 Studies have demonstrated that CH4 can be directly activated on the electrocatalyst surface such as NiO/Ni 28 and TiO2/RuO2/V2O5 29 , showing 13-97%CH3OH selectivity (Table S1).…”
mentioning
confidence: 99%
“…14,15,16,17,18 To address the issue of overoxidation by excessive amount of H2O2, the in situ synthesis of H2O2 from H2/O2 mixtures, catalyzed by AuPd bimetallic nanoparticles, has been integrated into CH4 oxidation processes. 19,20,21,22,23,24,25 Nonetheless, the cost of catalysts/oxidants and the employment of hazardous chemicals have limited the utility of those process.…”
mentioning
confidence: 99%